In‐hospital and one year outcomes with drug‐eluting versus bare metal stents in large native coronary arteries: A report from the evaluation of drug‐eluting stents and ischemic events registry. Issue 4 (25th May 2013) - Gordon, Paul C.; Cohen, David J.; Kleiman, Neal S.; Montgomery, Jay A.; Semder, Christopher A.; Kennedy, Kevin F.; Keyes, Michelle J.; Piana, Robert N.; ,
<x xml:space="preserve">Abstract</x> Objectives We sought to compare the clinical outcomes after perctuaneous coronary revascularization of large coronary arteries using drug‐eluting (DES) or bare‐metal (BMS) stents. Background In de novo native coronary lesions with reference diameters of 2.5–3.5 mm, DES reduce target lesion revascularization (TLR) with no increase in death or myocardial infarction (MI). The relative efficacy of DES in larger coronary artery lesions is less certain. Methods From the prospective Evaluation of Drug‐Eluting Stents and Ischemic Events registry, we identified patients undergoing stenting of de novo lesions in native coronary arteries 3.5–5.0 mm in diameter (n = 1, 485). In‐hospital and 1‐year clinical outcomes were compared for BMS (n = 282) and DES (n = 1, 203) patients, using propensity stratification to adjust for differences in potential confounding factors. Results Most patient characteristics were similar for the two groups, but BMS patients were more likely to have been treated in the setting of ST elevation MI, whereas DES patients had more bifurcation lesions, smaller vessels, and longer total stent lengths. In risk‐adjusted analyses, the composite endpoint of 1‐year death, MI or TLR was similar for BMS and DES (standardized rate: 11.9% vs. 8.5%, P = 0.10). DES was associated with a 62% reduction in the risk of TLR, although the absolute difference in event rates was small (standardized rates 4.6% vs. 1.8%, P = 0.016). Conclusions Among relatively unselected patients undergoing PCI of large native coronary arteries, use of DES was associated with a modest reduction in rates of TLR, with a neutral effect on other ischemic endpoints. © 2012 Wiley Periodicals, Inc.